Desain Augmented Reality Unit Rekam Medis di Rumah Sakit Citra Husada Jember - Deva Setia Pratama; Nugroho Setyo Wibowo (Politeknik Negeri Jember, 2020)
Hospital is a health-care institution that provides in-country, alternative health care, and emergency care. Good service must be sustained by sufficient means and infrastructure for each unit including a medical record. Medical records unit are still not up to standard resulting in disruption of employee’s effectiveness. A narrow room and files that stack up on the floor, filling room that's stuffy and narrow and filling that lack nighttime exposure becomes a constrained in the medical record unit. This research was aimed to redesign room of medical records in Hospital of Citra Husada Jember that according to the guidelines. The method is qualitative research with data collection technique observation, interview and brainwriting. The result of this research is redesign room of medical records based of the guidelines to realized ideal facilities and infrastructure for comfort the worked. Also manufactured augmented reality that useful for helped user to simulated room design previously form 2 dimensions pictures to 3 dimensions pictures. The improvement is a design which matches the anthropometrics units to the working facilities and menu programmed on augmented reality application.